ASAS NEBIS IN IDEM DALAM PUTUSAN HAKIM DALAM PERKARA POLIGAMI DI PENGADILAN NEGERI PASAMAN SEBAGAI CERIMINAN IUS CONSTITUTUM - Gokma Toni Parlindungan S (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The purpose of marriage cannot always be achieved in full. Usually the achievement is still at the stage of family formation or household formation, because it can be measured quantitatively. Whereas qualitatively that is happy and eternal can not be achieved, even not achieved at all. This is evident from the many divorces, betel marriages, and polygamy and this has an impact on the status and position of marriage, children and property. Such conditions are very alarming, because on the one hand marriage is a sacred institution, but on the other hand marriage does not have a sacred meaning, because it is triggered by various factors, including the economy.